Management of metabolic syndrome through probiotic and prebiotic interventions - Mallappa, Rashmi H. (Medknow Publications & Media Pvt Ltd, 2012)
Metabolic syndrome is a complex disorder caused by a cluster of interrelated factors that increases the risk of cardiovascular diseases and type 2 diabetes. Obesity is the main precursor for metabolic syndrome that can be targeted in developing various therapies. With this view, several physical, psychological, pharmaceutical and dietary therapies have been proposed for the management of obesity. However, dietary strategies found more appropriate without any adverse health effects. Application of probiotics and prebiotics as biotherapeutics is the new emerging area in developing dietary strategies and many people are interested in learning the facts behind these health claims. Recent studies established the role of probiotics and prebiotics in weight management with possible mechanisms of improved microbial balance, decreased food intake, decreased abdominal adiposity and increased mucosal integrity with decreased inflammatory tone. Hence, the above “Pharmaco-nutritional” approach has been selected and extensively reviewed to gain thorough knowledge on putative mechanisms of probiotic and prebiotic action in order to develop dietary strategies for the management of metabolic syndrome.